The effects of 8 weeks of group based step aerobic exercise (GBSAE) versus individual based step aerobic exercise (IBSAE) on weight management in obese young women - Hanafi, Wan Nabila Wan (2018)
INTRODUCTION: Consistent adherence to prescribed exercise is low for individuals who are overweight or obese due to low self-efficacy, poor mood status, and unfamiliar exercise technique. However, adherence has been shown to improve with the use of an instructor or with supervised activity. Meanwhile, there are barriers to exercising with an instructor such as instructor availability, lack of enjoyment of exercise, time constraints, and cost. An alternative to overcome some of these potential barriers is to exercise with video-guided exercise at home. PURPOSE: the aims of this present study is to investigate the effects of 8 weeks of group-based step aerobic exercise (GBSAE) versus individual-based step aerobic exercise (IBSAE) on weight management in obese young women in regard to body composition, cardiorespiratory fitness and exercise enjoyment. METHODS: Twenty subjects, obese young women (21-26 years old) with a BMI of Asian cut-off points range from (26 kg/m2 to 41 kg/m2) were subsequently being assigned into two groups with n=10 per group: group-based step aerobic exercise (GBSAE) and individual-based step aerobic exercise (IBSAE). In GBSAE group, step aerobic exercise was carried out for 70 minutes per session, three time per week for eight weeks and was supervised by an exercise instructor. While IBSAE group carried out a similar step aerobic exercise via pre-recorded video for 70 minutes per session, three time per week for eight weeks. Before and after 8 weeks of intervention, subject’s body composition, cardiovascular fitness and physical activity enjoyment were measured. RESULTS: The end of 8 weeks of intervention, significant different were found between groups where GBSAE reported significant decrease on body mass (p=0.035), BMI (p=0.032), fat percentage (p=0.012), fat mass (p=0.007) and waist-hip ratio (p=0.038). However, no significant different were found on fat free mass (p=0.578), cardiovascular fitness (p=0.463) and physical activity enjoyment (p=0.658) between groups after 8 weeks of intervention. Despite no significance difference reported on free fat mass, cardiovascular fitness and physical activity enjoyment, GBSAE showed higher improvement on these parameters compared to IBSAE group. CONCLUSION: The results of present study suggest that group-based intervention elicited more beneficial effects on achieving weight loss goals with regards to body composition, waist-hip ratio, cardiovascular fitness and physical activity enjoyment.